Puss in Boots - Bird , Lady (UK Penguin Random house, 2017)
The "Puss in Boots" book in Ladybird Readers Level 3 is published by Ladybird Books. The author of this specific version is not explicitly mentioned in the search results, but it is identified as being written for children learning to read in English and is part of the "Read It Yourself" series.